Small and medium-sized firms and the role of private industry in Hungary - Hrubi, László; Kraftné, Somogyi Gabriella (Discussion Papers, 1994)
The first large section of the present study reviews the economic and legal frameworks of small enterprises in Hungary. After discussing the preconditions of privatisation, the authors provide an analysis of macropolicy and the development of small enterprises covering more than a quarter of a century with a particular emphasis on growth opportunities of small firms in light of the prevailing economic policy of the given time. The third chapter provides an overview of the rules regarding the operation, the self-government, the possible transformation and the termination of small and medium-sized enterprises including insolvency and the laws related to market behaviour. This chapter is followed by an examination of the organisation and efficiency of the instution system of politics and economic policy concerning SMEs. The fifth chapter focuses on entrepreneurship and regional policy in Hungary. The second major part of the study presents the SME sector in Baranya county with a special emphasis on economic restructuring processes, the development and distribution of business organisations, and finally presents the results of a survey on the functioning of SMEs.